2012
DOI: 10.1186/1746-1596-7-135
|View full text |Cite
|
Sign up to set email alerts
|

Ezrin overexpression predicts the poor prognosis of gastric adenocarcinoma

Abstract: BackgroundEzrin is a cytoskeletal protein that is involved in tumor growth and invasion. It has been suggested that Ezrin expression plays an important role in tumor metastasis. This study is aimed to investigate the clinicopathological significance of Ezrin overexpression in gastric adenocarcinomas.MethodsEzrin protein expression was examined by immunohistochemistry in 26 normal gastric mucosa, 32 dysplasia, and 277 gastric adenocarcinomas. The relationship between Ezrin expression and the clinicopathological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 28 publications
(40 reference statements)
4
25
0
Order By: Relevance
“…Moreover, another study showed that promoter methylation of SFRPs gene family was correlated with the development of CC, which could be regarded as molecular biomarker for the screening of CC [23]. The Ezrin gene was up-regulated in many tumors such as pancreatic carcinoma, hepatocellular carcinoma, gastric cancer and breast cancer, and the up-regulation of the Ezrin gene might enhance the metastatic phenotype of tumors [8,9]. Since the Ezrin gene takes part in cell migration and cell recognition through the immune system, it may exert an direct effect on tumor progression [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, another study showed that promoter methylation of SFRPs gene family was correlated with the development of CC, which could be regarded as molecular biomarker for the screening of CC [23]. The Ezrin gene was up-regulated in many tumors such as pancreatic carcinoma, hepatocellular carcinoma, gastric cancer and breast cancer, and the up-regulation of the Ezrin gene might enhance the metastatic phenotype of tumors [8,9]. Since the Ezrin gene takes part in cell migration and cell recognition through the immune system, it may exert an direct effect on tumor progression [24].…”
Section: Discussionmentioning
confidence: 99%
“…As the first member of the Ezrin-RadixinMoesin (ERM) family, Ezrin is up-regulated in many tumors including pancreatic carcinoma, hepatocellular carcinoma, gastric cancer and breast cancer [8,9]. Ezrin is regarded as a scaffold protein which contributes to oncogenesis by linking cytoskeletal and membrane proteins [10].…”
Section: Introductionmentioning
confidence: 99%
“…After washing with PBS, the cells were counterstained with 49-6-diamidino-2-phenylindole (DAPI) (C1006, Beyotime, Shanghai, China), and the coverslips were mounted with Antifade Mounting Medium (P0126, Beyotime, Shanghai, China). Finally, the immunofluorescence signals were visualized and recorded by Leica SP5II confocal microscope (Jin et al, 2012).…”
Section: Immunofluorescence Staining For Six1 Protein In Pancreatic Cmentioning
confidence: 99%
“…Ezrin participates in various cellular processes relevant to aggressive tumor behavior and various phases of tumor metastasis (81,82). The immunohistochemical results from the analysis of436 GC samples demonstrated that high Ezrin expression in GC lesions was associated with LN and distant metastasis (83,84) (Table II).…”
Section: Other Mechanismsmentioning
confidence: 99%